Solve for y 27-y=-3(3y-1)

Math
27-y=-3(3y-1)
Simplify -3(3y-1).
Tap for more steps…
Apply the distributive property.
27-y=-3(3y)-3⋅-1
Multiply.
Tap for more steps…
Multiply 3 by -3.
27-y=-9y-3⋅-1
Multiply -3 by -1.
27-y=-9y+3
27-y=-9y+3
27-y=-9y+3
Move all terms containing y to the left side of the equation.
Tap for more steps…
Add 9y to both sides of the equation.
27-y+9y=3
Add -y and 9y.
27+8y=3
27+8y=3
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Subtract 27 from both sides of the equation.
8y=3-27
Subtract 27 from 3.
8y=-24
8y=-24
Divide each term by 8 and simplify.
Tap for more steps…
Divide each term in 8y=-24 by 8.
8y8=-248
Cancel the common factor of 8.
Tap for more steps…
Cancel the common factor.
8y8=-248
Divide y by 1.
y=-248
y=-248
Divide -24 by 8.
y=-3
y=-3
Solve for y 27-y=-3(3y-1)

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top